DIPG-72. TARGETING MULTIPLE PATHWAYS AS A TREATMENT STRATEGY IN DIFFUSE MIDLINE GLIOMA. Issue 2 (22nd June 2018) - Salacz, Michael; Murray, Donna; Kast, Richard
Abstract: BACKGROUND: Diffuse midline glioma (DMG) is an entity characterized by midline location, treatment refractoriness, short survival, and H3 histone mutation. DMG encompasses pediatric diffuse intrinsic pontine glioma (DIPG), as most (80%) harbor an H3 mutation as well. REPURPOSED DRUG THERAPY: DMGs require both H3 histone mutation and second mutated pathway for tumorigenesis. Minimally-toxic targeting with valproic acid and metformin (reverse H3 effects), simvastatin and vitamin D to inhibit hedgehog, sertraline for RTK-Ras, and temozolomide for cytotoxicity is proposed in combination with a mitotic inhibitor. MITOTIC INHIBITOR: Nativis Voyager ® system is a non-sterile, non-invasive, non-thermal, portable, investigational medical device that uses a specific, localized ultra-low radio frequency energy (ulRFE ® ) cognate, based on Lorenz Force, for the treatment of brain cancer. The AIA cognate is hypothesized to stabilize microtubule disassembly by changing the charge dynamics at the tubulin monomer subunit and strengthening the bond between monomers. CONCLUSIONS: Early data suggest the repurposed drug cocktail in combination with mitotic inhibition can provide a meaningful therapeutic and minimally toxic benefit in DMG. This type of approach using existing FDA-approved medications would speed protocol development from the bench to the bedside. A compassionate use study will begin enrolling pediatric patients, using the repurposed drug cocktail in combination with a newly developed Nativis Voyager Pediatric system. Clinical trial information: CT02296580